Factors Affecting Public Service Innovation At The Investment And One Stop Service Office, North Buton - Tawai, Adrian; Muchtasar, Fahril; Utha, Arifin (International Journal of Educational Research & Social Sciences, 2022)
Public service is a very important element in the administration of government because it involves very broad aspects of life and the government has the function of providing various public services needed, especially to meet the needs of the community in various aspects of life. This study aims to examine the factors that influence the innovation of public services at the Investment and One Stop Service Office of North Buton Regency. The research method using qualitative research is descriptively analyzed which is obtained directly from the results of observations, both document studies and documentation based on the facts at the research location. The results showed that the factors influencing public service innovation at the One Stop Investment and One Stop Service Office of North Buton Regency were political encouragement, economic pressure and increased efficiency, pressure to improve service quality, organizational culture and arrangement, rewards or incentives, inability to face risks. and change, short-term budgeting and planning, and a culture of risk aversion.